The Islamist Uprising in Syria, 1976–82: The History and Legacy of a Failed Revolt. Issue 4 (1st October 2016) - Lia, Brynjar
Abstract: The Islamist Uprising in Syria between 1976 and 1982 remains understudied in view of the growing availability of new primary sources on the subject. The present article explores the unfolding of the Revolt, examining the causes for its eventual defeat and the long-term legacy of the Uprising. It argues that the Islamist Uprising in Syria failed for a variety of reasons, first and foremost internal disunity and indecisiveness, leading to a lack of military preparedness, planning, and coordination at critical junctures, and a lack of mass mobilization for the Revolt. Failure to rally sufficient foreign support made the Uprising crumble in the face of the regime's unrestrained brutality. Rather than serving as a rallying cry for the Syrian opposition, the defeat at Hama has had a divisive effect, illustrated by the contradictory narratives embraced by the Syrian Muslim Brotherhood and their jihadi opponents.